Deletion of the amyloid precursor-like protein 1 (APLP1) enhances excitatory synaptic transmission, reduces network inhibition but does not impair synaptic plasticity in the mouse dentate gyrus - Vnenčák, Matej; Paul, Mandy H.; Hick, Meike; Schwarzacher, Stephan W.; Turco, Domenico Del; Müller, Ulrike C.; Deller, Thomas; Jedlicka, Peter (The journal of comparative neurology, 2015)
Amyloid precursor-like protein 1 (APLP1) is a transmembrane synaptic protein belonging to the amyloid precursor protein (APP) gene family. Although the role of this gene family—in particular of APP—has been intensely studied in the context of Alzheimer's disease, the physiological roles of its family members remain poorly understood. In particular, the function of APLP1, which is predominantly expressed in the nervous system, has remained enigmatic. Since APP has been implicated in synaptic plasticity, we wondered whether APLP1 could play a similar role. First, using in situ hybridization and laser microdissection combined with reverse transcription-quantitative polymerase chain reaction (PCR) we observed that Aplp1 mRNA is highly expressed in dentate granule cells. Having this examined, we studied synaptic plasticity at the perforant path-granule cell synapses in the dentate gyrus of APLP1-deficient mice in vivo. Analysis of field excitatory postsynaptic potentials evoked by stimulation of perforant path fibers revealed increased excitatory transmission in APLP1-deficient mice. Moreover, we observed decreased paired-pulse inhibition of population spikes indicating a decrease in network inhibition upon deletion of APLP1. In contrast, short-term presynaptic plasticity (STP) as well as long-term synaptic plasticity (LTP) was unchanged in the absence of APLP1. Based on these results we conclude that APLP1 deficiency on its own does not lead to defects in synaptic plasticity, but affects synaptic transmission and network inhibition in the dentate gyrus. J. Comp. Neurol. 523:1717-1729, 2015. © 2015 Wiley Periodicals, Inc.